2018
DOI: 10.1016/j.critrevonc.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of cancer metabolism

Abstract: Systemic approaches are needed and useful for the study of the very complex issue of cancer. Modeling has a central position in these systemic approaches. Metabolic reprogramming is nowadays acknowledged as an essential hallmark of cancer. Mathematical modeling could contribute to a better understanding of cancer metabolic reprogramming and to identify new potential ways of therapeutic intervention. Herein, I review several alternative approaches to metabolic modeling and their current and future impact in onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 58 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…These studies serve as examples of how systems biology approaches can be formulated and applied to probe cancer metabolism. A detailed review of the mathematical models of metabolism can be found in 98 . Future progress on using computational models to elucidate the coupled decision-making of EMT-MR must combine these independent studies after a careful assessment of their cross-talk.…”
Section: To Solve the Emt-mr Puzzle: Systems Biologymentioning
confidence: 99%
“…These studies serve as examples of how systems biology approaches can be formulated and applied to probe cancer metabolism. A detailed review of the mathematical models of metabolism can be found in 98 . Future progress on using computational models to elucidate the coupled decision-making of EMT-MR must combine these independent studies after a careful assessment of their cross-talk.…”
Section: To Solve the Emt-mr Puzzle: Systems Biologymentioning
confidence: 99%
“…Our work serves as a platform to target abnormal metabolism in cancer by modulating both genes and metabolic pathways. most widely used approaches to simulate cancer metabolism (23,24). Applications include quantifying the extent of aerobic glycolysis of the NCI-60 cell lines (25), characterizing their primary uptake pathways (26), and identifying the change of their metabolic states upon gene knockdown and/or drug treatment (27).…”
mentioning
confidence: 99%
“…Recently, some authors investigated that the patients prognosis of acute myeloid leukemia is due to cytokineindependent leukemic cell proliferation see [7]. Miguel [8] & Rodriguesa et.al [9], also contributed their results for cancer metabolism and presented a detailed mathematical model for chemoimmunotherapy for lymphocytic leukemia describing its normal conditions and stability analysis of immunotherapy. Leukemia and tumor based on several other mathematical models were studied by a few more researchers such as [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%